Optimization and Kinetic Studies of Enzymatic Saccharification of Double-Stage Ozonolysis Pretreated Oil Palm Empty Fruit Bunch for Enhanced Sugar Production - Nur Zahidah Abd Majid; Amnani Shamjuddin; Mohd Asmadi; Umi Aisah Asli; Sharifah Nurain Hussain; Nardiah Rizwana Jaafar; Gwendoline Christophe; Philippe Michaud; Riyani Tri Yulianti; Nur Hidayah Zainan; Asiah Nusaibah Masri (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
Oil Palm Empty Fruit Bunch (OPEFB), an abundant lignocellulosic biomass in Malaysia, is a promising feedstock for producing Total Reducing Sugar (TRS), although its recalcitrant structure limits enzymatic conversion. This study proposes a novel double-stage ozonolysis pretreatment integrated with intermediate alkaline swelling to enhance cellulose accessibility and saccharification efficiency. Structural modifications were confirmed through compositional analysis, TGA, XRD, FTIR, and SEM. Enzymatic saccharification (ES) was optimized using Response Surface Methodology (RSM) based on a Face-Centered Central Composite Design (FCCCD), evaluating reaction time, biomass loading, and temperature. Analysis of Variance (ANOVA) indicated a significant model (R2 = 0.88), with optimal conditions of 44 h reaction time, 1.8 % w/v biomass loading, and 50 °C temperature, achieving a maximum TRS yield of 42.75%. The double-stage ozonolysis outperformed single-stage and alkaline pretreatments, yielding the highest cellulose enrichment (up to 79 wt%) and improved digestibility. Kinetic analysis revealed a substantial reduction in the Michaelis-Menten constant ( ) from 175.713 to 9.010 mg/mL, indicating enhanced enzyme–substrate affinity. These findings demonstrate a robust and efficient strategy for improving biomass-to-sugar conversion. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).